2016
DOI: 10.1002/pits.21940
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Incremental Value of Kabc-Ii Luria Model Scores in Predicting Achievement: What Do They Tell Us Beyond the Mpi?

Abstract: The current study examined the incremental validity of the Luria interpretive scheme for the Kaufman Assessment Battery for Children‐Second Edition (KABC‐II) for predicting scores on the Kaufman Test of Educational Achievement‐Second Edition (KTEA‐II). All participants were children and adolescents (N = 2,025) drawn from the nationally representative KABC‐II/KTEA‐II linked standardization sample. Consistent with previous studies, the full scale Mental Processing Index (MPI) score accounted for clinically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…Whereas, related predictive validity studies with cognitive measures (e.g., Benson, Kranzler, & Floyd, 2016;Canivez, 2013a;McGill, 2015aMcGill, , 2015bMcGill & Spurgin, 2016) have largely suggested that broad and narrow cognitive abilities account for trivial portions of achievement after controlling for general ability, the present results suggest that this conclusion as a general rule may be overstated. As previously mentioned, although the GIA consistently accounted for large reading effects, lower-order scores accounted for meaningful incremental prediction in several circumstances.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Whereas, related predictive validity studies with cognitive measures (e.g., Benson, Kranzler, & Floyd, 2016;Canivez, 2013a;McGill, 2015aMcGill, , 2015bMcGill & Spurgin, 2016) have largely suggested that broad and narrow cognitive abilities account for trivial portions of achievement after controlling for general ability, the present results suggest that this conclusion as a general rule may be overstated. As previously mentioned, although the GIA consistently accounted for large reading effects, lower-order scores accounted for meaningful incremental prediction in several circumstances.…”
Section: Discussioncontrasting
confidence: 51%
“…Incremental validity studies using HMRA have been conducted previously on the WJ III COG (McGill, 2015a;McGill & Busse, 2015) and other related intelligence tests (e.g., Canivez, 2013a;McGill, 2015b;McGill & Spurgin, 2016). Across these studies, it was consistently demonstrated that the omnibus full scale IQ score accounted for most of the reliable achievement variance that could be predicted in the regression models and that little additional incremental variance was accounted for by the lower-order broad and narrow ability scores after controlling for the predictive effects of the general factor.…”
Section: Introductionmentioning
confidence: 90%
“…We did observe relationships between temporal variability of FCN and mental processing scale, which combines both sequential and simultaneous processing scales and is a measure of a child's overall level of cognitive processing McGill and Spurgin (2016). Interestingly, we observed that for the mental processing scale, both positive and negatively correlated network dynamics are important to distinguish between low and high-scoring children.…”
Section: Age-related Increase In Temporal Variabilitymentioning
confidence: 69%
“…Whereas a series of recent exploratory investigations failed to support the structural and predictive validity of Luria dimensions on the KABC‐II (e.g., McGill & Spurgin, , ), these studies were not dispositive for determining what psychological dimensions are measured by the Luria model. Accordingly, the purpose of the present study was to examine the structural validity of the Luria interpretive model across the school age (ages 7–18) using rival CFA procedures in an attempt to better disclose the latent structure of the Luria subtest configuration.…”
Section: Discussionmentioning
confidence: 95%